AB0067 ASSOCIATION BETWEEN INTERLEUKIN-6–174 G/C POLYMORPHISMS AND VASCULITIS: A META-ANALYSIS. (June 2019) - Jung, Jae Hyun; Song, Gwan Gyu; Kim, Jae-Hoon; Choi, Sung Jae
Abstract : Background: Interleukin (IL)-6 is associated with the development and progression of vasculitis, and inhibitors of this cytokine are used to treat this disease. Polymorphisms of the promoter region of IL-6 are associated with the production and expression of IL-6. Objectives: The aim of this study was to perform a meta-analysis of eligible studies to derive a precise estimate of the association between IL-6 polymorphisms and susceptibility to vasculitis. Methods: A meta-analysis was conducted on the associations between IL-6-174 G/C and vasculitis. The literature was searched using the PubMed and Embase databases to identify available articles in which IL-6 polymorphisms were analyzed in vasculitis patients. The associations between the -174 G/C alleles and vasculitis were estimated by evaluating odds ratio (OR) and 95% confidence interval (CI). We performed meta-analyses using the 1) allelic contrast (C vs. G), 2) recessive (CC vs. GC+GG), and 3) dominant (CC+GC vs. GG) models, and 4) heterozygote vs. dominant homozygote (GC vs. GG), 5) heterozygote vs. recessive homozygote (GC vs. CC), and 6) homozygote comparison (CC vs. GG). Results: A total of 13 studies involving 1, 294 vasculitis patients and 1, 594 controls were considered in the meta-analysis. There were significant associations between IL-6-174 G/C polymorphisms and vasculitis in allele contrast, dominant genetic model, and heterozygote vs. dominant homozygote comparison (OR 0.80, 95% CI 0.67–0.94, P =0.009 and OR 0.76, 95% CI 0.63–0.92, P =0.005, respectively). In subgroup analysis based on subtype, there were significant associations between IL-6 polymorphisms and susceptibility in large and medium vessel vasculitis, but not in small and variable vessel vasculitis. Conclusion: The GC genotype of IL-6-174 G/C was suggested by the analyses to be related to low prevalence of vasculitis, especially for large and medium vessels. References: [1] Assari R, Aghighi Y, Ziaee V, Sadr M, Rahmani F, Rezaei A, Sadr Z, Moradinejad MH, Raeeskarami SR, Rezaei N. (2018) Pro-inflammatory cytokine single nucleotide polymorphisms in Kawasaki disease. Int J Rheum Dis21:1120-6. [2] Berti A, Cavalli G, Campochiaro C, Guglielmi B, Baldissera E, Cappio S, Sabbadini MG, Doglioni C, Dagna L. (2015) Interleukin-6 in ANCA-associated vasculitis: Rationale for successful treatment with tocilizumab. Semin Arthritis Rheum45:48-54. [3] Salvarani C, Casali B, Farnetti E, Pipitone N, Nicoli D, Macchioni P, Cimino L, Bajocchi G, Catanoso MG, Boiardi L. (2005) Interleukin-6 promoter polymorphism at position -174 in giant cell arteritis. J Rheumatol32:2173-7. Acknowledgement: No grant or other support was received for this study. Disclosure of Interests: None declared